2019
DOI: 10.1016/j.toxrep.2019.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation of calcium L-methylfolate

Abstract: HighlightsThe toxicity of calcium L-methylfolate was studied.No toxic, mutagenic, teratogenic nor embryogenic effects were observed.The NOAEL for calcium L-methylfolate was 400 mg/kg bw/day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
(38 reference statements)
0
9
0
1
Order By: Relevance
“…Moreover, previous studies have demonstrated the excellent safety profile for the Calcium L-5-methyltetrahydrofolic acid (L-5-MTHF-Ca). Thus, it would be interesting to assess in future studies a supplementation with L-5-MTHF-Ca as a safe alternative to 5-MTHF as a source of folate, in particular for pregnant women carrying the MTHFR(677)T variant [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies have demonstrated the excellent safety profile for the Calcium L-5-methyltetrahydrofolic acid (L-5-MTHF-Ca). Thus, it would be interesting to assess in future studies a supplementation with L-5-MTHF-Ca as a safe alternative to 5-MTHF as a source of folate, in particular for pregnant women carrying the MTHFR(677)T variant [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…5-MTHF compared to folic acid was found to increase plasma folate levels more effectively [111]. Safety studies of high-dose 5-MTHF in rats showed no adverse events [112] and dosages as high as 17 mg of 5-MTHF daily for 12 weeks have been shown to have no side effects [113]. In pregnancy, there have been reported no side effects with 1.13 mg [114] and 7.5 mg and 15 mg 5-MTHF have been used without side effects in patients with depression [115,116].…”
Section: Folate Metabolismmentioning
confidence: 93%
“…The sham-operated group received a saline injection. A recent toxicity study revealed that daily oral administration of 5-MTHF (400 mg/kg) to rats for 13 weeks did not cause toxic effects on the kidneys and liver [ 40 ]. Rats with or without folic acid injection were sacrificed at 24 h after reperfusion.…”
Section: Methodsmentioning
confidence: 99%